2001
DOI: 10.1161/hy1201.096574
|View full text |Cite
|
Sign up to set email alerts
|

Role of the B 2 Receptor of Bradykinin in Insulin Sensitivity

Abstract: Abstract-The biological actions of bradykinin (BK) are attributed to its B 2 type receptor (B 2 R), whereas the B 1 R is constitutively absent, inducible by inflammation and toxins. Previous studies in B 2 R gene knockout mice showed that the B 1 R is overexpressed, is further upregulated by hypertensive maneuvers, and assumes some of the hemodynamic functions of the B 2 R. The current experiments were designed to further clarify the metabolic function of the B 2 R and to explore whether the upregulated B 1 R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 48 publications
6
70
1
1
Order By: Relevance
“…The first finding is that BRKO mice are insulin resistant, which is in agreement with a previous report that B2R-null mice are insulin-resistant (51). Thus the KKS may play an important role in insulin sensitivity in mice.…”
Section: Discussionsupporting
confidence: 91%
“…The first finding is that BRKO mice are insulin resistant, which is in agreement with a previous report that B2R-null mice are insulin-resistant (51). Thus the KKS may play an important role in insulin sensitivity in mice.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that bradykinin influences glucose metabolism through both insulindependent and insulin-independent pathways (Motoshima et al 2000). It has been shown that the administration of bradykinin increases glucose uptake in cultured adipocytes and skeletal muscles of the forearm in humans (Duka et al 2001). In addition, bradykinin reduces hyperinsulinemia, decreases the concentration of plasma free fatty acids, improves glucose tolerance, increases insulin action in target tissues (Henriksen et al 1998) and enhances glucose transport through exercise (insulin-independent pathway) (Kishi et al 1998).…”
Section: Bradykininmentioning
confidence: 99%
“…Duka et al 5 showed that the lean B2KO mice have significantly higher steady-state insulin levels, significantly lower glucose uptake rates and insulin sensitivity indexes, but did not analyze hepatic gluconeogenesis. We challenged these lean mice with the pyruvate tolerance test (Supplementary Figure S1) and we also carried out hepatic mRNA expression analysis of some gluconeogenesis factors (FoxO1, G6Pase, PEPCK and PGC-1; Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…The kallikrein-kinin system (KKS) modulates pain, vasodilatation, vascular permeability, inflammation and edema and has been linked to insulin resistance. [4][5][6][7] Bradykinin (BK), the agonist of the constitutively expressed BK B2 receptor (BKB2R), has been reported to increase glucose uptake in skeletal muscle and adipose tissue. 8 At the same time, the kinin B1 receptor and its agonist, the des-arg 9 -kinin, have been shown to control leptin sensitivity 7 and insulin secretion.…”
mentioning
confidence: 99%